Nerventransplantation: operative Techniken - Ayache, Ali; Unglaub, Frank; Cavalcanti Kußmaul, Adrian; Spies, Christian; Langer, Martin Franz (Operative Orthopädie und Traumatologie, 2024)
Objective Peripheral nerve lesions often lead to significant and permanent loss of motor and sensory function. The aim of peripheral nerve grafting is to bridge nerve defects. Indications When tension-free nerve repair is not possible, peripheral nerve grafting is indicated. Contraindications Local infection, insufficient soft tissue coverage, significant muscle atrophy or joint contraction in case of “motor” nerve grafting, lack of microsurgical instruments or experience, life-threatening injuries. Surgical technique Exposure and preparation of the nerve stumps. Choosing and preparation of the donor nerve. Approximation. Nerve repair. Nerve reconstruction must always be tension-free as nerve repair with tension frequently leads to disruption of nerve healing and poor functional outcome. Autologous nerve grafting from various donor sites leads to excellent functional results with little sensory deficits at the donor regions. Postoperative management Limited immobilization, physiotherapy, ergotherapy, regular clinical and neurological assessments. Results Outcome of peripheral nerve grafting may, for example, depend on defect length, caliber and quality of the injured nerve, quality of the donor nerve, microsurgical expertise of the surgeon, time of reconstruction, and age of the patient.